2011
DOI: 10.1145/1978782.1978790
|View full text |Cite
|
Sign up to set email alerts
|

Max-coloring and online coloring with bandwidths on interval graphs

Abstract: Given a graph G = (V, E) and positive integral vertex weights w : V → N, the max-coloring problem seeks to find a proper vertex coloring of G whose color classes C 1 , C 2 , . . . , C k , minimizemax v∈C i w(v). This problem, restricted to interval graphs, arises whenever there is a need to design dedicated memory managers that provide better performance than the general purpose memory management of the operating system.Though this problem seems similar to the dynamic storage allocation problem, there are fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…First we prove that the incomparability graph of every poset of width w without k + k has small pathwidth, namely pathwidth at most (2k − 3)w − 1. Then we show that the fact that First-Fit uses at most 8w chains on interval orders of width w, as proved in [20], implies that First-Fit uses at most 8(p + 1) chains on posets whose incomparability graphs have pathwidth p. Combining these two results, we obtain an upper bound of 8(2k − 3)w on the number of chains used by First-Fit on posets of width w without k + k.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…First we prove that the incomparability graph of every poset of width w without k + k has small pathwidth, namely pathwidth at most (2k − 3)w − 1. Then we show that the fact that First-Fit uses at most 8w chains on interval orders of width w, as proved in [20], implies that First-Fit uses at most 8(p + 1) chains on posets whose incomparability graphs have pathwidth p. Combining these two results, we obtain an upper bound of 8(2k − 3)w on the number of chains used by First-Fit on posets of width w without k + k.…”
Section: Introductionsupporting
confidence: 53%
“…If no such chain is found, then a new chain containing only v is added at the end of the current chain partition. The performance of First-Fit on various classes of posets has been studied extensively [1,3,4,5,6,10,14,16,22,18,19,20]. In particular, Kierstead [14] showed that First-Fit can be forced to use an unbounded number of chains even on posets of width 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kierstead and Qin [11] subsequently improved the bound, showing that FF(w) ≤ 25.8w. Later, Pemmaraju, Raman, and Varadarajan [16] (see also [17]) proved that FF(w) ≤ 10w with an elegant argument known as the Column Construction Method. Their proof was later refined by Brightwell, Kierstead, and Trotter [5] and independently by Narayanaswamy and Babu [15] to show that FF(w) ≤ 8w.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, this also provides the first proof that some on-line algorithm uses o(w 2 ) chains on (r + s)-free posets. Our proof is strongly influenced by the Column Construction Method of Pemmaraju et al [17] and can be viewed as a generalization of that technique from interval orders to (r + s)-free posets.…”
Section: Introductionmentioning
confidence: 99%